Environmental concern and government regulations roles in influencing ecologically conscious consumer behaviour / Wan Kalthom Yahya - Yahya, Wan Kalthom (Universiti Teknologi MARA, Cawangan Melaka, 2019)
Environmental concerns have increased dramatically in recent decades. Individuals have become more concerned with their purchasing behaviour and the impact on the environment. As a result, marketers tend to be more committed in responding to the needs and desires of these individuals in a more responsible manner, considering possible environmental damages that may occur. This study pursued to establish the relationship between young consumers and ecologically conscious consumer behaviour (ECCB) by analysing their green environmental concerns (EC) and government regulations (GR) variables. The scope of the study was UiTM’s students ages between 18 to 30 years old pursuing their undergraduate studies. The Statistical Package for the Social Sciences (SPSS) version 23 is applied to study the hypotheses. The results from the linear multiple regression analysis indicated that both EC and GR had a positive relationship on ECCB. Moreover, the overall results have confirmed that the government regulations have a strong direct influence on ecologically conscious consumer behaviour. Thus, the findings could offer important young consumers’ perceptions and views on environmental sustainability.